Sharing works and copyright issues in massive open online courseware (MOOC) - Wahid, Ratnaria; Mohd Sani, Azizuddin; Mat, Bakri; Subhan, Muhammad; Saidin, Khaliza (2015)
Various higher education institutions around the world have been adopting the Massive Open Online Courseware (MOOC), a new technological means to distribute and share knowledge across borders. While technology deem it convenient to share works online, the copyright issue cannot be taken for granted since it may lead to unnecessary legal actions that will hamper constructive teaching and learning. It is necessary to have clear awareness on the copyright issues and to understand what strategy could be used to provide a secure and positive MOOC environment. This paper is aimed at identifying and explaining the relationship between works sharing and copyright issues in MOOC environment. The paper highlighted strategies that can be undertaken by someone who want to share their works that fall under the public domain, creative common licenses and open access repositories